The antibacterial potential of curly red chili pepper (Capsicum annuum L.) fruit stem waste against foodborne disease bacteria - Dwi Susanti; Salsabilla Ardi Wardhani; Agustina Retnaningsih (Jurnal Penelitian Saintek, 2026)
Foodborne diseases remain a global health problem, commonly caused by bacteria such as Salmonella typhi, Escherichia coli, Bacillus cereus, and Staphylococcus aureus. The utilization of natural materials, such as curly red chili pepper fruit stem waste with antimicrobial activity, may serve as an alternative natural treatment for infections caused by these pathogens. This study aimed to evaluate the antibacterial potential of curly red chili pepper (Capsicum annuum L.) fruit stem waste extract as a natural antibacterial agent. The waste material was extracted using a maceration method with 96% ethanol as the solvent. The extract was qualitatively analyzed through phytochemical screening, which revealed the presence of flavonoids, saponins, tannins, alkaloids, steroids, and phenolic compounds. Antibacterial activity was evaluated using the disc diffusion method at extract concentrations of 100%, 90%, 80%, and 70%. The results showed that all concentrations produced inhibition zones categorized as “resistant” according to CLSI standards, with ciprofloxacin as the positive control and distilled water as the negative control. The 100% extract concentration exhibited the largest inhibition zone, with the mean inhibition zones against Bacillus cereus and Staphylococcus aureus (Gram-positive bacteria) being greater than those against Salmonella typhi and Escherichia coli (Gram-negative bacteria). These findings indicate that curly red chili pepper fruit stem extract possesses weak antibacterial activity and requires further investigation.